Application of sulfur ylides in 1,2-difunctionalization of arynes via insertion into a C-S sigma-bond - Ahire, Milind M.; Thoke, Mahesh B.; Mhaske, Santosh B. (Organic Letters, 2018)
A novel reactivity of sulfur ylides has been demonstrated in a transition-metal-free protocol to access ortho-substituted thioanisole derivatives by insertion of arynes into a C-S sigma-bond in moderate to good yields. The reaction involves the formation of C-C and C-S bonds and consecutive breaking of two C-S bonds under operationally mild reaction conditions.